Kedisiplinan Kovenan Spiritual: Model Kepemimpinan Visioner Perempuan Berbasis Nilai Pesantren - Ubaidillah Ubaidillah; Sunardi Sunardi; Riyadlotus Sholichah; Nina Nuriyah Ma’arif; Ach. Shobri (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2026)
Mainstream literature on student discipline management often relies on behaviorist paradigms (punishment and surveillance) and overlooks the effectiveness of nurturing women's leadership roles in educational institutions. This study aims to fill this gap by analyzing a model of visionary women's leadership grounded in pesantren (Islamic boarding school) values to enhance student discipline. Employing a qualitative case study approach at MI Al-Urwatul Wutsqo in Jombang, data were collected through in-depth interviews, participant observations, and documentation, and subsequently analyzed using the Miles and Huberman interactive model. The findings indicate that the women's leadership model in this madrasah represents an integrative synthesis of visionary-managerial, maternal-nurturing, and uswah spiritual (spiritual exemplar) roles. Through the internalization of pesantren values particularly uswah hasanah (good role modeling) and a dialogic maternal approach, the leadership successfully transformed rule compliance from a mechanical level into an internalized awareness. Theoretically, this study offers an alternative perspective to classical Behaviorism (Operant Conditioning) and Foucault's Panopticon surveillance concept by introducing the notion of Spiritual Covenant Discipline. In contrast to conventional discipline driven by the fear of physical sanctions, Spiritual Covenant Discipline is motivated by the values of ta'dzim (reverence) and the pursuit of barakah (divine blessing), proving to be more persistent, autonomous, and sustainable. The research concludes that spiritual values and a maternal approach can serve as an epistemological foundation for robust and humanistic student behavior management.